ASSESSMENT OF THYROID DYSFUNCTIONS IN PATIENTS WITH TYPE II DIABETES MELLITUS IN CENTRAL INDIA - TOMAR, MUKESH SINGH; MELWANI, VEENA; TRIVEDI, ANSHULI (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The objective of the study was to assess the prevalence of thyroid disorders among diabetics in Central India. Methods: This study was conducted as a cross-sectional comparative study at the department of medicine, tertiary care center in Central India on a total of 100 diabetic patients admitted at the study area during the study period of 1 year. Cases in the study group with diabetes and control group (non-diabetic) were enrolled as per inclusion and exclusion criteria in 1:1 ratio. All the patients in both the groups were subjected to the estimation of thyroid function tests, that is, T3, T4, and TSH levels after overnight fasting. Results: Mean age of patients in the study group was 55.7±10.1 years whereas that of the control group was 53.9±10.6 years. Overall, thyroid dysfunctions were noted in 31% of cases in the study group and 12% of cases in the control group (p<0.05). The most common thyroid dysfunction was hypothyroidism, particularly subclinical hypothyroidism (19% and 8% in the study group and control group, respectively). Thyroid dysfunctions were associated with increased HbA1c in our study group (p<0.05). Conclusion: Thyroid dysfunctions are observed in higher proportions of cases with diabetes as compared to non-diabetes. All the parameters of thyroid function tests including T3 and T4 levels as well as TSH levels are found to be altered in higher number of diabetics. Poor glycemic control among diabetics is one of the important determinants of thyroid dysfunction in patients with diabetes.